A Study on the Level of Awareness for Sustainable Construction Management Among Contractors in Malaysia - Ismail, Maziahtul Akmar; Hasmori, Muhammad Fikri (Recent Trends in Civil Engineering and Built Environment, 2024)
The development of the construction industry has led to environmental issues. The negative environmental implications have led to an increase that there is a need for a more sustainable and accountable approach especially to construction players in addressing environmental issues. Limited number of sustainable project in Malaysia show that building industry is at primarily at the early stage of adopting the notion of sustainability. This research objectives is to identify the level of awareness of sustainable construction management among contractors in Malaysia and the challenges for the implementation of sustainable construction at construction sites especially among contractor grade G1 to G7 in Selangor state. The technique of identifying elements was gathered through extensive literature research. The research conducted via questionnaire. The questionnaire were evaluated by expert review to fit the unique industrial context. Changes are made to the the questionnaire based on comments from an expert review before it is completed and used in the survey. Questionnaires was then distributed to industry player in construction industry. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) software. The Cronbach's alpha approach is used as the internal consistency in reliability analysis. . From the data collection and analysis, as conclusion, the level of awareness among the contractors is adequate and respective parties have to get a first move to make it awareness among construction player. It is hoped that in the future the level of awareness of contractors on sustainable construction management will increase especially in the Malaysian construction industry.